The case of the hungry stranger - Bonsall, Crosby Newell, 1921- (New York : HarperTrophy, 1992)
Wizard and his friends are clueless when they are sent on the trail of a blueberry pie thief--until he hits on a plan that is sure to nab the sweet-toothed pilferer.
13 38
Keywords: Mystery and detective stories